1998
DOI: 10.2516/ogst:1998007
|View full text |Cite
|
Sign up to set email alerts
|

Study of Asphaltene Solutions by Electrical Conductivity Measurements

Abstract: Les interactions des asphalt•nes avec leur environnement molŽculaire dans des solutions mod•les ont ŽtŽ ŽtudiŽes par la mesure de la conductivitŽ Žlectrique de ces solutions. Les interactions avec le n-heptane, des rŽsines, des tensioactifs, l'eau, le phŽnol et le chlorure de sodium ont ŽtŽ explorŽes. Les conclusions tirŽes de cette Žtude ont confirmŽ certaines hypoth•ses faites sur les mŽcanismes d'agrŽgation des asphalt•nes en solution, en particulier dans le cadre de la thŽorie des solutions collo•dales. ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…They used electrical and optical methods to determine the onset of asphaltene precipitation and concluded that combining these two techniques improves the interpretation of experimental results. Behar et al (1998) studied the effect of asphaltene concentration in solutions of asphaltenes in nitrotoluene and THF by conductivity measurements. They repeated their experiments on solutions of asphaltenes in nitrotoluene in the presence of resins.…”
Section: Density Measurement Methodsmentioning
confidence: 99%
“…They used electrical and optical methods to determine the onset of asphaltene precipitation and concluded that combining these two techniques improves the interpretation of experimental results. Behar et al (1998) studied the effect of asphaltene concentration in solutions of asphaltenes in nitrotoluene and THF by conductivity measurements. They repeated their experiments on solutions of asphaltenes in nitrotoluene in the presence of resins.…”
Section: Density Measurement Methodsmentioning
confidence: 99%
“…It is observed that destabilization of colloidal asphaltene in oil production systems may occur if the surface charge and the resulting attraction forces between adsorbed resins and asphaltenes are disturbed (Leontaritis 1989;Alkafeef 2001). Later works of Fotland and Anfindsen (1996) and Behar et al (1998) on electrical conductivity of asphaltene helped in understanding their molecular association phenomena in solution phase, while works of Igor and Aleksander (2010) on electrical conductivity of solid asphaltenes showed that asphaltenes in solid state behave like semiconductors, conductivity increasing at higher temperature, possibly due to structural phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…59 Electrical conductivity studies showed that resins can neutralize part of the asphaltene charges by adsorbing on their surface. 65 The stability of asphaltenes in petroleum fluids can also be disrupted by several other stimuli, including pressure, temperature, concentration, and composition of the injected solvents, e.g., steam, CO 2 , nitrogen, methane, etc. However, the process of asphaltene aggregation and precipitation is more sensitive to pressure than other thermodynamic and process parameters.…”
Section: Asphaltene Structurementioning
confidence: 99%
“…87,95 However, in nitrotoluene, resins were shown to decrease the DC conductivities of asphaltene clusters. 65 In a heptane/toluene mixture, resins have a propensity to aggregate with asphaltene, decrease the conductivity, and enhance their stability in the mixture. 59 3.4.…”
Section: Electrical Properties Of Asphaltenesmentioning
confidence: 99%
See 1 more Smart Citation